Application of the RASCH model to analyze Critical Thinking Skills Instruments (CTSI) on static fluid concept - Lingga Thursina Fajriyati; Duden Saepuzaman; Lina Aviyanti; Winny Liliawati (Momentum: Physics Education Journal, 2026)
This study aims to analyze the reliability, validity of item analysis, and estimation of respondents' abilities in assessing students' critical thinking skills (CTS) instrument on static fluid material using the Rasch model. There are five indicators of the CTS instrument, namely Basic Clarification (BCL), Decision Basis (TBD), Inference (INF), Advanced Clarification (ACL), and Assumption and Integration (SIN), with a total of 20 items. The Rasch model was chosen because it provides an in-depth analysis of item characteristics, respondents' abilities, and allows the identification of imprecise or biased items. Although the theoretical background is presented briefly due to the methodological focus of this study, previous studies have primarily emphasized improving CTS through learning interventions rather than developing standardized measurement instruments. The research method used is quantitative with a descriptive design using Win steps 3.73 software for data analysis. The sample consisted of 215 high school students in grades XI and XII majoring in science, consisting of 120 female students and 95 male students in West Java. The results of the study showed that the test instrument had high reliability with an individual reliability of 0.73 and an item reliability of 0.92, as well as good internal consistency with a Cronbach's Alpha of 0.78. The validity of this instrument also met the acceptance criteria of the Rasch model, with MNSQ infit and MNSQ outfit values ​​ranging from 0.5 to 1.5, indicating acceptable model fit. Therefore, the CTS test instrument is suitable for use in high school physics education. This study contributes to addressing the limited availability of validated CTSCTS instruments specifically designed for static fluid material at the high school level using Rasch analysis.